Dominant Cultural and Personal Stigma Beliefs and the Utilization of Mental Health Services: A Cross-National Comparison - Bracke, Piet; Delaruelle, Katrijn; Verhaeghe, Mieke (Frontiers in Sociology, 2019)
Purpose: The detrimental impact of stigma on the utilization of mental health services is a well-established finding. Nevertheless, most studies consider only the personal or interactional dimensions of stigma. This contribution makes a distinction between the dominant beliefs about stigma within a culture and the personal beliefs of individuals with regard to stigma. We hypothesize that both have an impact on professional-care seeking within the field of mental health. Methods: A multi-level research design is used to estimate the effects of both types of stigma beliefs on the likelihood of consulting general and specialized health professionals about mental health problems in 28 European countries (N of individuals = 24,881, Eurobarometer 248, 2005–2006). Results: In countries where stigmatizing beliefs are dominant, the likelihood of seeking help from specialized mental health professionals is constrained, and individuals refrain from contacting general practitioners when in need of formal support, regardless of their own personal stigma beliefs. Conclusion: The present study signals the importance of stigma beliefs as shared cultural phenomena, and of personal stigma beliefs to the likelihood of seeking professional care for mental health problems. We therefore propose that most studies on stigma and formal-care seeking underestimate the pervasive effects of stigma beliefs, due to methodological individualism.